Selected issues of penalisation in penal economic law. Remarks on the crimes against economic circulation Chapter XXXVI of Criminal Code - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The study examines the present model of penalty sanctions for crimes against economic circulation defined in chapter XXXVI of the Criminal Code. It also presents institutions allowing to toughen or mitigate the repression in that field. In the given normative context, the judicial system in cases of crimes against economic circulation Chapter XXXVI Criminal Code in the years 2010–2015 was analyzed.
Keywords: prawo karne gospodarcze; przestępstwa gospodarcze; przestępstwa przeciwko obrotowi gospodarczemu; statystyka przestępstw przeciwko obrotowi gospodarczemu